Fungicide Sensitivity of Sclerotinia homoeocarpa from Golf Courses in Ohio - Jo, Young-Ki (Plant disease, 2006)
Managing dollar spot, the most common and chronic disease on intensively cultivated turfgrass, relies on the judicious use of fungicides. The heavy use of fungicides has led to the development of isolates of Sclerotinia homoeocarpa insensitive to several classes of fungicides, including benzimidazoles, demethylation-inhibitors, and dicarboximides. In vitro fungicide sensitivity assays using single discriminatory concentrations of thiophanate-methyl, propiconazole, and iprodione were developed in this study for evaluating field efficacy of these fungicides and the prevalence of fungicide insensitivity within S. homoeocarpa isolated from golf courses throughout Ohio. Discriminatory concentrations for these fungicides were determined to be: thiophanate-methyl = 1,000 μg a.i. ml-1, propiconazole = 0.1 μg a.i. ml-1, and iprodione = 1.0 μg a.i. ml-1. Effective concentration that produces 50% inhibition (EC50) was estimated based on relative mycelial growth of S. homoeocarpa on potato dextrose agar (PDA) versus PDA amended with the discriminatory concentration of each fungicide. Field trials conducted at 3 locations in 2002 and 10 locations in 2003 revealed that the in vitro assays accurately predicted field efficacy for thiophanate-methyl. When used to screen 192 S. homoeocarpa isolates collected previously from 55 golf courses throughout Ohio, the in vitro assays revealed that 34 of the golf courses sampled had S. homoeocarpa resistant to thiophanate-methyl. S. homoeocarpa with reduced in vitro sensitivities was isolated from 18 and 1 golf courses for propiconazole and iprodione, respectively